Broadband optical limiting in nanohybrids of graphene grafted peripheral (non-peripheral) pyrene substituted phthalocyanines with a low linear absorption. (January 2023) - Makhseed, Saad; Sebastian, Mathew; Ganesan, Asaithampi; Husain, Ali
Graphical abstract: Highlights: Non-covalently functionalized graphene-peripheral (non-peripheral) pyrene substituted phthalocyanine nanohybrids have been prepared. These nanohybrids, possess very low linear absorption throughout a broad range of wavelengths, exhibit a good broadband optical nonlinearity. A specific shift of 8 cm −1 for the Raman 2D peak is observed in the prepared nanohybrids, which is a clear evidence of non-covalent interaction in graphene-pyrene based material hybrids. Nonlinear optical studies prove these nanohybrids as broadband optical limiters with low optical limiting threshold. Abstract: In nonlinear optics, nanohybrids from the functionalization of graphene and organic molecules can be an interesting area of research. In this work, nanohybrid materials consisting of pyrene conjugated peripheral phthalocyanines and non-peripheral phthalocyanines, which are non-covalently attached to the graphene exhibit broadband optical characteristics and broadband limiting optical behavior through a two-photon absorption process with a high degree of transparency. For confirming non-covalent functionalization, optical as well as spectroscopic studies like UV–vis absorption, fluorescence studies, transient absorption, FTIR, XPS, Raman, AFM techniques, etc., were employed. Distinct morphologies are observed for these nanohybrids, such as -nanohybrids with a cylindrical shape in the non-peripheral case whereas a conical shaped nanohybrids in the peripheral case. Furthermore, Raman studies reveal a shift of 8 cm −1 for the 2D peak of both nanohybrids in comparison with that of graphene confirms the strong π-π interaction, which is the maximum shift in a non-covalent interaction between pyrene attached graphene. In a major finding, a donor-acceptor combination is established in these nanohybrids, which makes them important nonlinear optical materials. The nonlinear absorption coefficients of 112 ± 7 cm/GW and 228 ± 12 cm/GW were obtained for these nanohybrids. Compared to the existing reported values, these nanohybrids with the minimum linear absorption coefficient (1.15 cm −1 and 1.25 cm −1 ), display broadband nonlinear optical characteristics with low optical limiting thresholds (0.9 and 0.83 Jcm −2 ), which is achieved through the transfer of electrons from Pc core to pyrene anchored graphene, enable them standout candidates for photonic applications.